2020
DOI: 10.17576/jskm-2020-1801-02
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relationship of Body Mass Index and Waist Circumference on the Image Quality of Abdominal Computed Radiography

Abstract: Body sizes of patients undergoing x-ray examination vary in body mass index (BMI) and waist circumference (WC). This study aimed to evaluate the relationship between BMI and WC on the image quality of abdominal computed radiography (CR). Anteroposterior supine abdomen projection was conducted on 69 patients from Hospital Raja Perempuan Bainun, Ipoh using a Siemens Multixtop general x-ray unit, and the images were processed with CR Carestream Direct view Max. Samples were categorised into normal BMI (n = 23), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…16,17 The WC is a more suitable and simple body measurement method for obese patients than body mass index (BMI) because high WC reveals that patients have high central obesity. 18 For dose measurement, results showed that the radiation dose delivered to patients by DAP measurement was suitable, and provided a good estimate of the total radiation energy delivered during a procedure, being directly related to the amount of radiation produced by the X-ray tube. 19 Our results showed DAP reduction when using high kVp, concurring with previous research reporting that DAP decreased at higher kV and copper filtration.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The WC is a more suitable and simple body measurement method for obese patients than body mass index (BMI) because high WC reveals that patients have high central obesity. 18 For dose measurement, results showed that the radiation dose delivered to patients by DAP measurement was suitable, and provided a good estimate of the total radiation energy delivered during a procedure, being directly related to the amount of radiation produced by the X-ray tube. 19 Our results showed DAP reduction when using high kVp, concurring with previous research reporting that DAP decreased at higher kV and copper filtration.…”
Section: Discussionmentioning
confidence: 99%
“…In studies with phantoms, the distribution of adipose tissue at the anatomical area of interest was an important factor in determining the resultant image quality [42][43][44][45] . In their study with a pelvis phantom, Ismail et al, [44] reported a higher negative correlation (r = -0.83, p < 0.01) between the waist circumference and the image quality for abdominal images compared to that of the BMI and image quality (r = -0.73, p < 0.01).…”
Section: General Radiographymentioning
confidence: 99%
“…In studies with phantoms, the distribution of adipose tissue at the anatomical area of interest was an important factor in determining the resultant image quality [42][43][44][45] . In their study with a pelvis phantom, Ismail et al, [44] reported a higher negative correlation (r = -0.83, p < 0.01) between the waist circumference and the image quality for abdominal images compared to that of the BMI and image quality (r = -0.73, p < 0.01). To penetrate the increased anatomical area thickness, MRPs usually adopt higher exposure factors which result in decreased SNR, increased motion artifacts due to the long exposure times, increased entrance skin dose and scatter radiation which degrade the overall image quality [17] .…”
Section: General Radiographymentioning
confidence: 99%